Human health risk assessment due to Cadmium accumulation through consumption of Chinese cabbage grown in Cadmium-contaminated soil (Journal of Biodiversity Conservation and Bioresource Management, 2018)
Heavy metal like Cadmium (Cd) is a common pollutant present in the soils of urban and industrial areas. Vegetables are preferably grown in these soils than other crops. Of the vegetables, Chinese cabbage (Brassica campestris var. pekinensis) is gaining its popularity among farmers for its high market value. Therefore, an experiment was conducted where cabbage was grown on Cd treated soil. Bioaccumulation of Cd in Chinese cabbage was determined and Target Hazard Quotient (THQ) model was used to assess potential health risk of human. Results showed that with increasing concentration of added Cd (0.00 to 4.00 ppm) in soil, bio-concentration factors of Cd of Chinese cabbage also increased except at 4 ppm. The chinese cabbage grown in Cd contaminated soils up-to 1.00 ppm might be safe. However, cabbage grown in the soils contaminated with Cd above this level would probably be risky and may cause serious health hazard to human body.J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(1): 1-8